Student perspective on distance online learning experience during the COVID-19 pandemic in undergraduate pharmacy program in UiTM: pharmacology of CNS drugs / Mizaton Hazizul Hasan, Aisyah Hasyila Jahidin and Yuslina Zakaria - Hazizul Hasan, Mizaton; Jahidin, Aisyah Hasyila; Zakaria, Yuslina (UiTM Press, 2022)
The method of teaching and learning (T&L) has changed radically due to the COVID-19 pandemic, globally. Schools and universities had to adapt to a new T&L experience by moving into hybrid learning or fully electronic online mode. As for the third-year pharmacy students in UiTM, the Faculty of Pharmacy employed 100% online distance learning (ODL). Hence, this study aims to evaluate the third-year pharmacy student ODL experience during the COVID-19 pandemic on one of the core subjects, Pharmacology of Central Nervous System (CNS) Drugs. The online survey was distributed to students at the end of the semester. Multiple questions made up a score that reflects their perspective on the subject relevant to the ODL experience. The survey was voluntary, and all data were collected and recorded via google forms. The response rate was about 74% (n=186). The results' analysis revealed some variable responses. The ODL experience poses many challenges not only to the students but lecturers alike. The burden of completing assignments and at the same time coping with the current situation of an unconducive environment at home with internet instability has pushed the students to almost a breaking point. Hence, a more structured plan needs to be implemented to ensure the students have the best for their academic development to pursue their professional careers without compromising their soft skills.